Simplified Irregular Beam Analysis and Design - Mohammed Salem Al-Ansari; Muhammad Shekaib Afzal (Salehan Institute of Higher Education, 2019)
This paper presents simple method to estimate the strength design of reinforced concrete beam sections based on structural safety and reliability. Irregular beam shaped sections are commonly used nowadays in the construction industry. This study reveals the simplified method to analyze and design the different irregular shaped beam sections. In this study, the selected irregular beam shaped sections are divided mainly into three groups, beams with straight edges, beams with sloped edges and circular beams. Each group contains the most commonly used beam shaped sections in that category. Six beams sections (B-1 to B-6) are selected for group-1 whereas five beam sections (B-7 to B-11) and a circular beam section (B-12) are chosen for group 2 and 3 respectively. Flexural beam formulas for three groups of reinforced concrete beams are derived based on section geometry and ACI building code of design. This study also analyzed numerical examples for some of the sections in each group category using the proposed simplified method to determine the strength design of the irregular beams. The results obtained using simplified method for all of the three groups are compared with the finite element software (SAP v2000). The percentage difference of simplified method with the finite element software ranges within 5% to 10%. This makes the simplified method for irregular shaped beam sections quite promising.